Evolution of monogenetic rift-related alkaline magmatism in south Egypt: Insight from stratigraphy, geochronology, and geochemistry of the Natash volcanics. (November 2018) - Khalaf, Ezz El Din Abdel Hakim; Sano, Takashi; Tsutsumi, Yukiyasu
Abstract: The Mesozoic Natash volcanics are rift-related monogenetic volcanic complex that erupted in south Eastern Desert of Egypt. The architecture of their building has evolved through three phases namely: (1) tuff cone consisting of explosive -dominated pyroclastics that stand for an intensity eruption peak; (2) the effusive lava-conquered phase, characterized by prevalent basalt-trachyte-rhyolite fissure eruptions; and (3) late-stage subvolcanic plugs/domes. The first phase began with the emplacement of spatter-rich ignimbrites followed by grain-supported lapilli-tuffs and hyaloclastics in a shallow-water environment (phreatomagmatic phase) with a vent-opening phase. This initial phase is followed by deposition of clast-supported conglomerates of lahar facies that represent significant erosional period, separating the pyroclastics and effusive phases. The second phase comprises multiphases displaying compositional stratification (primitive beneath evolved) of pahoehoe Hawaiian and rubbly vulcanian lavas, overlying the pyroclastic deposits. The third phase is the youngest and comprises plugs of aphyric trachytes. The volcanics occasionally have vesicle sheets, cylinder-elongate vesicles, gas blister, and inflation clefts, reflecting degassing, rupturing, brecciation/quenching history, and pressurized flows. U-Pb zircon ages from two samples of trachyte volcanics gave concordant age of 92 ± 0.9 Ma. One trachyte plug yielded concordant age of 86.6 ± 1.3 Ma. These ages represent two events belonging to the major Senonian volcanic activities. The investigated volcanics have alkaline affinity and display a continuous composition ranging from basalt to trachyte and rhyolite. Their chemical compositions display linear, curvilinear, and scattered trends on the Harker diagrams matched with the petrographic data and reflect comagmatic genesis for the entire sequence. Crystal fractionation of olivine + pyroxene + plagioclase + Fe-Ti oxides + apatite plays a role in the volcanic evolution. The origin of the mafic rocks is derived from deep mantle source in the garnet facies via low degree of partial melting. Such magma source is affected by fluid-rich metasomatism generated by dehydration subducted crust on the EM I, EMII, and HIMU mantle reservoir during Neoproterozoic time. The basalt-trachyte-rhyolite suites and their pyroclastics from the Natash area, together with Mesozoic alkaline volcanics from the surrounding terrains in Africa, constitute a remnant of extensive magmatisms, having large extension, high eruption rate, and OIB-type chemical composition. Graphical abstract: Image 1 Highlights: Displaying the stratigraphical, petrographical, geochronological, and geochemical characteristics of Mesozoic Natash volcanics, SE Egypt. Deducing the nature of their magma source. Presentation the successive eruptive phases controlling the volcanic architecture. Highlighting the relationship of Natash volcanics and the surrounding areas in NE Africa.